Morphological and transcriptomic effects of endocrine modulators on the gonadal differentiation of chicken embryos: The case of tributyltin (TBT). (1st March 2018) - Scheider, Jessica; Afonso-Grunz, Fabian; Jessl, Luzie; Hoffmeier, Klaus; Winter, Peter; Oehlmann, Jörg
Highlights: A phenotypic anchoring of whole-transcriptomic changes in chicken gonads. Induced by the endocrine disrupter TBT. Enables the cross-linking of phenotypic changes to underlying molecular mechanisms. Abstract: Morphological malformations induced by tributyltin (TBT) exposure during embryonic development have already been characterized in various taxonomic groups, but, nonetheless, the molecular processes underlying these changes remain obscure. The present study provides the first genome-wide screening for differentially expressed genes that are linked to morphological alterations of gonadal tissue from chicken embryos after exposure to TBT. We applied a single injection of TBT (between 0.5 and 30 pg as Sn/g egg) into incubated fertile eggs to simulate maternal transfer of the endocrine disruptive compound. Methyltestosterone (MT) served as a positive control (30 pg/g egg). After 19 days of incubation, structural features of the gonads as well as genome-wide gene expression profiles were assessed simultaneously. TBT induced significant morphological and histological malformations of gonadal tissue from female embryos that show a virilization of the ovaries. This phenotypical virilization was mirrored by altered expression profiles of sex-dependent genes. Among these are several transcription and growth factors (e.g. FGF12, CTCF, NFIB), whose altered expression might serve as a set of markers for early identification of endocrine active chemicals that affect embryonic development by transcriptome profiling without the need of elaborate histological analyses.